Rakesfall ebook - Chandrasekera, Vajra (2024)
Rakesfall is a groundbreaking, standalone science fiction epic about two souls bound together from here until the ends of time, from the author of The Saint of Bright Doors. Some stories take more than one lifetime to tell. There are wrongs that echo through the ages, friendships that outpace the claws of death, loves that leave their mark on civilization, and promises that nothing can break. This is one such story. Annelid and Leveret met as children in the middle of the Sri Lankan civil war. They found each other in a torn-up nation, peering through propaganda to grasp a deeper truth. And in a demon-haunted wood, another act of violence linked them and propelled their souls on a journey throughout the ages. No world can hold them, no life can bind them, and they'll never leave each other behind. Tracing two souls through endless lifetimes, Rakesfall is a virtuosic exploration of what stories can be. As Annelid and Leveret reincarnate ever deeper into the future, they will chase the edge of human possibility in a dark science fiction epic unlike anything you've read before. At the Publisher's request, this title is being sold without Digital Rights Management Software (DRM) applied.